2016
DOI: 10.1016/j.drugalcdep.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine abuse and effects in the serum levels of cytokines IL-6 and IL-10

Abstract: Our results suggest that cocaine users showed an activation of the immune system when compared a control group, demonstrating a disruption in the balance of pro and antiinflammatory cytokines. Thus, peripheral cytokines may represent a putative biomarkers for cocaine users, contributing to the development of diagnosis and effective treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…This process can justify the reduction of triglycerides and visceral fat area in the GOLD 3 group. Recently, IL-6/IL-10 ratio has been used as a good marker for degree inflammatory status with several diseases and conditions, such as AIDS, polytrauma, drugs abuse [41][42][43]. Thus, IL-6/IL-10 ratio could be an interesting strategy to prevent severity disease earlier.…”
Section: Discussionmentioning
confidence: 99%
“…This process can justify the reduction of triglycerides and visceral fat area in the GOLD 3 group. Recently, IL-6/IL-10 ratio has been used as a good marker for degree inflammatory status with several diseases and conditions, such as AIDS, polytrauma, drugs abuse [41][42][43]. Thus, IL-6/IL-10 ratio could be an interesting strategy to prevent severity disease earlier.…”
Section: Discussionmentioning
confidence: 99%
“…High secretion of IL-10 following partial activation of microglia following binge drinking has also been postulated to demonstrate the reparative role of microglia (Marshall et al, 2013). Interestingly, recent studies have also indicated attenuated basal levels of IL-10 in both early abstinent (Fox et al, 2012b) and actively using (Moreira et al, 2016) cocaine dependent individuals. Moreover, following three weeks of cocaine abstinence, a dampened IL-10 response was similarly observed following cocaine cue imagery compared with controls and concomitant to elevations in cocaine craving (Fox et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to identify these possible biomarkers by exploring accessible signaling compartments (i.e., blood) or functional neuropsychological tests. Among these attempts, recent studies have identified circulating factors involved in immune function as potential biomarkers in CUD and other substance use disorders ( Araos et al, 2015 ; Moreira et al, 2016 ; García-Marchena et al, 2017a ). These and other studies have demonstrated that abused drugs interact with the immune system and alter signaling and gene expression involved in the immune response, which these effects contribute to various aspects of addiction ( Cui, Shurtleff & Harris, 2014 ).…”
Section: Introductionmentioning
confidence: 99%